Saving a Life by Recognizing the Rash: Niacin (Vitamin B3) Deficiency in Hartnup Disease With a Clinical Debut in Adulthood - Melanie Hafdi; Inge C.M. Hoogland; Arne A. Meesters; Mirjam Langeveld; Diederik van de Beek (Annals of Internal Medicine: Clinical Cases)
Tryptophan deficiency can lead to a critical shortness of niacin (vitamin B3), causing photosensitive dermatitis and a range of neurologic symptoms. The most common cause is severe protein malnutrition. However, in the case we present here, it is caused by a rare genetic disorder (Hartnup disease). A previously healthy 26-year-old woman presented with a photosensitive skin rash, myoclonic twitching of hands and mouth, and, ultimately, coma and status epilepticus. Starting treatment with high-dose niacin, even before the suspected diagnosis was confirmed, turned out to be a lifesaving intervention.